Lever idiomen i svenska ordböcker sitt eget liv? - Skjöldberg, Emma (Nordiske Studier i Leksikografi, 2001)
This article presents a study of 40 Swedish idioms. Firstly it focusses on to what degree the expressipns are listed in five contemporary Swedish dictionaries, and secondly to what extent the stated form of the expressions in the dictionaries corresponds to the actual usage af the expressions as they are reflected in the text corpus Parole. Among other things, the study indicates that there is good correspondence in approxirnately half of the cases. However in other cases the differences are more apparent. For example one often sees a distinct variation in the usage of an idiom in Parole, but this variation does not appear in the dictionaries. In other cases the opposite is true, i.e. the usage in Parole is relatively homogeneous but, in spite of this, alternative forms are shown in the dictionaries. The principal aim of the study is to initiate a discussion on the principles that are applied when listing idioms in dictionaries and on whether text corpora are utilised to their full potential.